Star ware : - Harrington, Philip S. (John Wiley, 2007)
In this revised and updated Fourth Edition of the essential guide to comparing and selecting sky-watching equipment, award-winning astronomy writer Philip Harrington takes you telescope shopping the easy way. He analyzes and explains today's astronomy market and compares brands and models point by point. Star Ware gives you the confidence you need to buy the telescope and accessories that are right for you and the knowledge to get the most out of your new purchase